The impact of organizational commitment and employee engagement among employees in Plaza Perangsang, Shah Alam / Munirah Ibrahim - Ibrahim, Munirah (Faculty of Business and Management, 2017)
The general purpose of this research is to investigate the impacts of organizational commitment on employee engagement among employees in the organization. The organizational commitment measured by three elements which are affective commitment, normative commitment and continuance commitment. Individual that have organizational commitments are common to recognised their own strength and weaknesses in order to identify which duties that they perform at their best. If the task is perfectly done, this will provide satisfaction to the individuals performing it as well as improving their weaknesses on certain aspects. This study uses probability sampling technique specifically of simple random sampling. A survey uses questionnaires and was distributed on a sample of 165 employees in Plaza Perangsang, Shah Alam Selangor. In the findings, it shows that the employees who have high engagement and organizational commitment will have high levels of affective commitment and normative commitment. On the other organizational commitment, high emplooyees‟ engagement can affect employees‟ continuance commitment. In this study has made significant contribution to the knowledge of the relationship between organizational commitment and employee engagement through examining the impact of various measurements.